Marginal microfiltration in amalgam restorations. Review - Lahoud Salem, Víctor (2005)
The present articule is review references from phenomenon of microfiltration in restorations with amalgam and yours consecuents in changes of color in the interface tooth-restorations, margin deterioted , sensitivity dentinarea postoperate, caries secondary and pulp inflamation. Besides naming the mechanicals for to reduce microfiltration, and yours effects for use of sealers dentinaries representation for the varnish cavitys and adhesive systens Conclusive indicate wath the amalgam is the materials to most use in the back sector. Also indicate walh whem the very large of the openíng interface tooth -amalgam is relative big ls possibily to present pronounced postoperative sensitivity.